2018
DOI: 10.1088/1674-1137/42/1/015101
|View full text |Cite
|
Sign up to set email alerts
|

Direct couplings of mimetic dark matter and their cosmological effects

Abstract: The original mimetic model was proposed to take the role of dark matter. In this paper we consider possible direct interactions of the mimetic dark matter with other matter in the universe, especially the standard model particles such as baryons and photons. By imposing shift symmetry, the mimetic dark matter field can only have derivative couplings. We discuss the possibilities of generating baryon number asymmetry and cosmic birefringence in the universe based on the derivative couplings of the mimetic dark … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…This generalized mimetic model has many applications in cosmology, and can provide us inflation, dark energy, bounce and so on with appropriate choice of the potential V (φ). The mimetic constraint can also be applied in various modified gravity models [8][9][10][11][12][13][14][15][16][17][18][19], and mimetic gravity has attracted extensive astrophysical and cosmological interests [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The Hamiltonian analysis of various mimetic models have also been investigated in refs.…”
Section: Introductionmentioning
confidence: 99%
“…This generalized mimetic model has many applications in cosmology, and can provide us inflation, dark energy, bounce and so on with appropriate choice of the potential V (φ). The mimetic constraint can also be applied in various modified gravity models [8][9][10][11][12][13][14][15][16][17][18][19], and mimetic gravity has attracted extensive astrophysical and cosmological interests [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The Hamiltonian analysis of various mimetic models have also been investigated in refs.…”
Section: Introductionmentioning
confidence: 99%
“…As commented in [12], the role of the Lagrange multiplier in the mimetic gravity formulation is to mimic a matter sector contribution that deviates from the standard behavior, 3 , given that we are considering the inclusion of a potential for the mimetic field. The explicit expression for the Lagrange multiplier is given in (11). One could assume that the observed deviation from the usual term can be due to an possible interaction of the matter sector with other components.…”
Section: Second Scenario: Interaction In the Dark Sectormentioning
confidence: 99%
“…In Ref. [11] was found that these kind of interactions can be possible only with derivative couplings of the mimetic field, but, these interactions can have a direct impact on observables of our Universe such as the CMB.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [20] was found that these kind of interactions can be possible only with derivative couplings of the mimetic field, but, these interactions can have a direct impact on observables of our Universe such as the CMB.…”
Section: Introductionmentioning
confidence: 99%